Mechanical behavior and failure of sandwich structures - Gdoutos, Е. (Автоматическая сварка, 2013)
The failure behavior of composite sandwich beams under three- and four-point bending was studied. The beams were made of unidirectional carbon/epoxy facings and various core materials including PVC closed-cell foams, a polyurethane foam and an aluminum honeycomb. Various failure modes including facing wrinkling, indentation failure and core failure were observed and compared with analytical predictions. It was established that the initiation, propagation and interaction of failure modes depend on the type of loading, constituent material properties and geometrical dimensions.